(Absence of) Association Between Non–Vitamin K Antagonist Oral Anticoagulant Therapy and Urinary Tract Infection in Patients With Atrial Fibrillation. Issue 6 (June 2021) - Heidemann, Jana; Tanislav, Christian; Kostev, Karel
Abstract : Abstract: The aim of the present study is to identify a potential association of urinary tract infections (UTI) in a large population of patients receiving oral anticoagulation therapy treated in general practices in Germany. This study contains patients diagnosed with atrial fibrillation who received at least one prescription of either non–vitamin K antagonist oral anticoagulation (NOAC) or vitamin K antagonists (VKA) within January 2015 and December 2018. The incidence of UTI was examined cumulatively on the basis of Kaplan–Meier methods and was complemented by incidence rates measured in cases per 1000 patient years. Sex-stratified Cox regressions were conducted to examine possible associations in specific sex groups. The study comprised 26, 934 patients receiving NOAC therapy and 8121 patients treated with VKA agents. Within a period of 5 years, slightly more NOAC than VKA users were diagnosed with UTI (20.3% vs. 19.3%), whereas the incidence rate was slightly higher in patients receiving NOAC therapy than in those under VKA treatment (50.8 cases vs. 50.5 cases in 1000 patient years). There was no significant association between direct oral anticoagulants versus vitamin K antagonists and infections of the urinary tract. Our study did not identify any significant association between therapy with direct oral anticoagulants versus vitamin K anticoagulants and UTI in patients diagnosed with atrial fibrillation in general practices in Germany. Because current findings regarding the risk of UTI in patients receiving oral anticoagulation therapy remain limited and contradictory, further investigations including a broad patient population are necessary to determine patients at risk for UTI and reconcile conflicting evidence.